iPLA2β deficiency attenuates obesity and hepatic steatosis in ob/ob mice through hepatic fatty-acyl phospholipid remodeling - Deng, Xiuling; Wang, Jiliang; Jiao, Li; Utaipan, Tanyarath; Tuma-Kellner, Sabine; Stremmel, Wolfgang; Chamulitrat, Walee (Biochimica et biophysica acta. Molecular and cell biology of lipids, 2016)
PLA2G6 or GVIA calcium-independent PLA2 (iPLA2β) is identified as one of the NAFLD modifier genes in humans, and thought to be a target for NAFLD therapy. iPLA2β is known to play a house-keeping role in phospholipid metabolism and remodeling. However, its role in NAFLD pathogenesis has not been supported by results obtained from high-fat feeding of iPLA2β-null (PKO) mice. Unlike livers of human NAFLD and genetically obese rodents, fatty liver induced by high-fat diet is not associated with depletion of hepatic phospholipids. We therefore tested whether iPLA2β could regulate obesity and hepatic steatosis in leptin-deficient mice by cross-breeding PKO with ob/ob mice to generate ob/ob-PKO mice. Here we observed an improvement in ob/ob-PKO mice with significant reduction in serum enzymes, lipids, glucose, insulin as well as improved glucose tolerance, and reduction in islet hyperplasia. The improvement in hepatic steatosis measured by liver triglycerides, fatty acids and cholesterol esters was associated with decreased expression of PPARγ and de novo lipogenesis genes, and the reversal of β-oxidation gene expression. Notably, ob/ob livers contained depleted levels of lysophospholipids and phospholipids, and iPLA2β deficiency in ob/ob-PKO livers lowers the former, but replenished the latter particularly phosphatidylethanolamine (PE) and phosphatidylcholine (PC) that contained arachidonic (AA) and docosahexaenoic (DHA) acids. Compared with WT livers, PKO livers also contained increased PE and PC containing AA and DHA. Thus, iPLA2β deficiency protected against obesity and ob/ob fatty liver which was associated with hepatic fatty-acyl phospholipid remodeling. Our results support the deleterious role of iPLA2β in severe obesity associated NAFLD.
Gesehen am 29.10.2019
Im Titel ist "ob/ob" kursiv geschrieben